Efficacy and tolerance of second-generation antipsychotics in anorexia nervosa: A systematic scoping review. - Solène Thorey; Corinne Blanchet; Sélim Benjamin Guessoum; Marie Rose Moro; Maude Ludot; Emilie Carretier (PLoS ONE)
Introduction Second-generation antipsychotics (SGAs) are frequently prescribed for the treatment of resistant anorexia nervosa. However, few clinical trials have been conducted so far and no pharmacological treatment has yet been approved by the Food and Drug Administration. The aim of this paper is to conduct a systematic scoping review exploring the effectiveness and safety of atypical antipsychotics in anorexia nervosa (AN). Method We conducted a systematic scoping review of the effectiveness and tolerability of SGAs in the management of AN. We included articles published from January 1, 2000, through September 12, 2022 from the PubMed and PsycInfo databases and a complementary manual search. We selected articles about adolescents and adults treated for AN by four SGAs (risperidone, quetiapine, aripiprazole or olanzapine). This work complies with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for scoping reviews (PRIMA-ScR) and was registered in the Open Science Framework (OSF) repository. Results This review included 55 articles: 48 assessing the effectiveness of SGAs in AN and 7 focusing only on their tolerability and safety. Olanzapine is the treatment most frequently prescribed and studied with 7 randomized double-blind controlled trials. Other atypical antipsychotics have been evaluated much less often, such as aripiprazole (no randomized trials), quetiapine (two randomized controlled trials), and risperidone (one randomized controlled trial). These treatments are well tolerated with mild and transient adverse effects in this population at particular somatic risk. Discussion Limitations prevent the studies both from reaching conclusive, reliable, robust, and reproducible results and from concluding whether or not SGAs are effective in anorexia nervosa. Nonetheless, they continue to be regularly prescribed in clinical practice. International guidelines suggest that olanzapine and aripiprazole can be interesting in severe or first-line resistant clinical situations.